Mitoepigenetics and Neurodegenerative Diseases - Coppedè, Fabio; Stoccoro, Andrea (Frontiers in Endocrinology, 2019)
Mitochondrial impairment and increased oxidative stress are common features in neurodegenerative disorders, leading researchers to speculate that epigenetic changes in the mitochondrial DNA (mitoepigenetics) could contribute to neurodegeneration. The few studies performed so far to address this issue revealed impaired methylation levels of the mitochondrial regulatory region (D-loop region) in both animal models, postmortem brain regions, or circulating blood cells of patients with Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis. Those studies also revealed that mtDNA D-loop methylation levels are subjected to a dynamic regulation within the progression of the neurodegenerative process, could be affected by certain neurodegenerative disease-causative mutations, and are inversely correlated with the mtDNA copy number. The methylation levels of other mtDNA regions than the D-loop have been scarcely investigated in human specimens from patients with neurodegenerative disorders or in animal models of the disease, and evidence of impaired methylation levels is often limited to a single study, making it difficult to clarify their correlation with mitochondrial dynamics and gene expression levels in these disorders. Overall, the preliminary results of the studies performed so far are encouraging making mitoepigenetics a timely and attractive field of investigation, but additional research is warranted to clarify the connections among epigenetic changes occurring in the mitochondrial genome, mitochondrial DNA dynamics and gene expression, and the neurodegenerative process.